2009
DOI: 10.1111/j.1471-4159.2009.06037.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular calcium deficiency plays a role in neuronal death caused by proteasome inhibitors

Abstract: Cytosolic Ca2+ concentration ([Ca2+]i) is reduced in cultured neurons undergoing neuronal death caused by inhibitors of the ubiquitin proteasome system. Activation of calcium entry via voltage-gated Ca2+ channels restores cytosolic Ca2+ levels and reduces this neuronal death (Snider et al. 2002). We now show that this reduction in [Ca2+]i is transient and occurs early in the cell death process, before activation of caspase-3. Agents that increase Ca2+ influx such as activation of voltage-gated Ca2+ channels or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Indeed, perturbation of proteasome activity has been shown to affect calcium dynamics in neurons 13,14 . Consistent with these findings, we observed that acute addition of the pan-proteasome inhibitor MG-132 onto neurons suppressed neuronal activity-induced calcium signaling (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, perturbation of proteasome activity has been shown to affect calcium dynamics in neurons 13,14 . Consistent with these findings, we observed that acute addition of the pan-proteasome inhibitor MG-132 onto neurons suppressed neuronal activity-induced calcium signaling (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that proteasome inhibitors induce a wide range of cellular changes, including imbalanced oxidative status (Keller et al, ; Lee et al, ), calcium dyshomeostasis (Lee et al, ; Wu et al, ), protein aggregation (Wyttenbach et al, ; Berke and Paulson, ), and regulation of transcription factor activity (Pye et al, ; Cai et al, ). To avoid nonspecific effects resulting from larger doses, we used the doses at a maximum of 1 1μM, which is at least about ten‐fold lower than the doses applied in previous studies (Bush et al, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome inhibition results in phosphorylation of eIF2α via activation of general control nonderepressible 2 (GCN2) in mouse embryonic fibroblasts, leading to reductions in protein synthesis (Jiang and Wek, ). We have found that proteasome inhibition can deplete ER calcium stores in primary mouse neurons (Wu et al, ); depletion of ER calcium is one type of ER stress (Paschen, ; Peters and Raghavan, ). Considering that proteasome inhibition usually induces protein aggregation, which may impact the ER protein quality‐control system, we examined whether and how proteasome inhibition changes the CRT/CNX glycoprotein quality‐control system and underlying mechanisms.…”
mentioning
confidence: 99%
“…The two major garbage disposal systems, the proteasome and the autophagy/lysosome apparatus, become dysfunctional in AD [90, 91]. Excessive elevations of intracellular Ca 2+ levels may impair proteasome function and autophagy [92, 93] on the one hand, while impaired proteasome and autophagy activity can result in dysregulation of cellular Ca 2+ homeostasis [94, 95] on the other hand.…”
Section: The Aging Brain Ii: Impaired Abilities To Prevent and Repmentioning
confidence: 99%